Br2 induced oxidative pore modification of a porous coordination network. Issue 2 (8th December 2015) - Ohtsu, Hiroyoshi; Kawano, Masaki
Abstract : Iodinated pores of a Zn-based coordination network were modified by Br2 oxidation to produce brominated pores in a polycrystalline-to-polycrystalline manner while maintaining the same network topology. Abstract : Iodinated pores of a Zn-based coordination network were modified by Br2 oxidation to produce brominated pores in a polycrystalline-to-polycrystalline manner while maintaining the same network topology. Ab initio X-ray powder diffraction analysis and Raman spectroscopy revealed that the brominated pore can trap Br2 or I2 by strong σ/π-type interactions. A kinetic study in solution revealed that the pore modification by Br2 oxidation is much faster than the Br2 encapsulation process.